Effects of surface tension time-evolution for CCN activation of a complex organic surfactant. Issue 2 (8th January 2020) - Lin, Jack J.; Kristensen, Thomas B.; Calderón, Silvia M.; Malila, Jussi; Prisle, Nønne L.
Abstract : Time-evolving partitioning effects on surface tension and bulk water activity cancel out in Köhler predictions of CCN activation of mixed NAFA–NaCl particles. Abstract : The physical processes and time scales underlying the evolution of surface tension in atmospheric solution droplets are largely unaccounted for in present models describing cloud droplet formation. Adsorption of surface-active molecules at the surface of a solution droplet depresses the droplet surface tension but also depletes solute from the droplet bulk, which have opposing and sometimes canceling effects in cloud droplet formation. In this work, we study the effect of time-evolving surface tension for cloud droplet activation of particles composed of Nordic Aquatic Fulvic Acid (NAFA) mixed with sodium chloride (NaCl). We model the formation of cloud droplets using Köhler theory with surface tension depression and bulk/surface partitioning evaluated from two different thermodynamic surface models. Continuous ternary parameterizations were constructed from surface tension measurements of macroscopic droplets at different time steps after the formation of a droplet surface. The predicted results are compared to previous measurements of mixed NAFA–NaCl cloud condensation nuclei (CCN) activity and a bulk solution model that does not take the NAFA bulk/surface partitioning equilibrium into account. Whereas the bulk model shows a trend in cloud droplet formation following that of macroscopic surface tension depression with time, the variation with time essentially disappears when bulk/surface partitioning is taken explicitly into account during droplet activation. For all equilibrium time steps considered, the effect of surface tension depression in the NAFA–NaCl system is counteracted by the depletion of solute from the finite-sized droplet bulk phase. Our study highlights that a comprehensive data set is necessary to obtain continuous parameterizations of surface tension and other solution properties required to fully account for the bulk/surface partitioning in growing droplets. To our knowledge, no similar data set currently exists for other aqueous organic systems of atmospheric interest. Additional work is necessary to deconvolve the effects of bulk/surface partitioning in the context of time-evolution on cloud droplet activation and to determine whether the results presented here can be further generalized.